Meta-Analysis Study of Think-Pair-Share Strategy on English Language Teaching and Learning in Indonesia - Elismawati Elismawati; Hidayat Al Azmi; Hadeli Hadeli; Zulyusri Zulyusri; Ahmad Syukri (Ta'dib, 2021)
This study aimed to analyze the effectiveness of the Think-Pair-Share strategy towards English teaching and learning. This research used a meta-analysis study. The technique of collecting data was coding datasheets. The researcher has to code the information of the research articles of journals about using the Think-Pair-Share strategy in English teaching and learning. The measurement of effect size analyzed the data. The research findings revealed that the overall effect size of the Think-Pair-Share strategy in English teaching and learning was calculated at 1.41 or in the category of large effect. The Think-Pair-Share is an influential and effective language teaching strategy in terms of the region in Indonesia, with an effect size of 1.67 in Sumatra, 1.2 in Java, and 1.18 in Sulawesi. Besides, based on educational level, the effect size is 1.25 in Junior High School, 1.61 in Senior High School, and 0.98 in university. Meanwhile, the effect size on students' English skills is 1.84 in speaking, 1.67 in reading, and 0.9 in writing. It can be concluded that the Think-Pair-Share strategy is effective to apply in English teaching and learning because it has a high impact in any educational level and region and enhances students' English skills in many aspects. Therefore, it is recommended that English teachers and curriculum designers implement and develop a Think-Pair-share strategy in the ELT classroom to enhance students’ English language skills.